Conceptual framework for the definition of preclinical and prodromal frontotemporal dementia. Issue 7 (7th December 2021) - Benussi, Alberto; Alberici, Antonella; Samra, Kiran; Russell, Lucy L.; Greaves, Caroline V.; Bocchetta, Martina; Ducharme, Simon; Finger, Elizabeth; Fumagalli, Giorgio; Galimberti, Daniela; Jiskoot, Lize C.; Le Ber, Isabelle; et al.
Abstract: The presymptomatic stages of frontotemporal dementia (FTD) are still poorly defined and encompass a long accrual of progressive biological (preclinical) and then clinical (prodromal) changes, antedating the onset of dementia. The heterogeneity of clinical presentations and the different neuropathological phenotypes have prevented a prior clear description of either preclinical or prodromal FTD. Recent advances in therapeutic approaches, at least in monogenic disease, demand a proper definition of these predementia stages. It has become clear that a consensus lexicon is needed to comprehensively describe the stages that anticipate dementia. The goal of the present work is to review existing literature on the preclinical and prodromal phases of FTD, providing recommendations to address the unmet questions, therefore laying out a strategy for operationalizing and better characterizing these presymptomatic disease stages.